Genomic insights into genetic diversity and local adaptation of a dominant desert steppe feather grass, Stipa breviflora Griseb. - Yan, Dongqing; Liu, Jiamei; Fan, Yanyan; Lian, Zhi; Dang, Zhenhua; Niu, Jianming (Frontiers in Plant Science, 2023)
Investigating the genetic mechanisms of local adaptation is critical to understanding how species adapt to heterogeneous environments. In the present study, we analyzed restriction site-associated DNA sequencing (RADseq) data in order to explore genetic diversity, genetic structure, genetic differentiation and local adaptation of Stipa breviflora. In total, 135 individuals were sequenced and 25,786 polymorphic loci were obtained. We found low genetic diversity (He = 0.1284) within populations of S. breviflora. Four genetic clusters were identified along its distribution range. Mantel test, partial Mantel test, and Multiple Matrix Regression with Randomization (MMRR) support that population differentiation was caused by both geographic distance and environmental factors. By FST outlier test and environmental association analysis (EAA), 113 candidate loci were identified as putatively adaptive loci. RPK2 and CPRF1, which are associated with meristem maintenance and light responsiveness, respectively, were annotated. To explore the effects of climatic factors on genetic differentiation and local adaptation of S. breviflora, 25,786 SNPs and 113 candidate loci were applied to gradient forest (GF) analysis respectively. The results showed that both temperature and precipitation affected the genetic differentiation of S. breviflora, and precipitation was strongly related to the local adaptation. Our study provides a theoretical basis for understanding local adaptation of S. breviflora.